2015
DOI: 10.1016/j.antiviral.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro combinations containing Tegobuvir are highly efficient in curing cells from HCV replicon and in delaying/preventing the development of drug resistance

Abstract: Tegobuvir (GS-9190) is a non-nucleoside inhibitor of HCV RNA replication with proven antiviral activity in HCV-infected patients. The in vitro antiviral activity of Tegobuvir, when combined with one or two other direct acting antivirals (DAA) was assessed. When Tegobuvir was combined with either interferon α-2b, ribavirin, the protease inhibitor (PI) VX-950, the nucleoside polymerase inhibitor (NI) 2'-C-methylcytidine or various non-nucleoside polymerase inhibitors, an overall additive antiviral activity was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Tegobuvir is a non-nucleoside inhibitor of hepatitis C virus (HCV) RNA replication with proven antiviral activity in the patients suffering from chronic genotype 1 HCV infection. Tegobuvir is an analog of imidazopyridine class inhibitors that selectively targets HCV (Vliegen et al., 2015 ). However, the most common side effects of Tegobuvir includes cough, dizziness, fatigue and dry mouth (Vliegen et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tegobuvir is a non-nucleoside inhibitor of hepatitis C virus (HCV) RNA replication with proven antiviral activity in the patients suffering from chronic genotype 1 HCV infection. Tegobuvir is an analog of imidazopyridine class inhibitors that selectively targets HCV (Vliegen et al., 2015 ). However, the most common side effects of Tegobuvir includes cough, dizziness, fatigue and dry mouth (Vliegen et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a trial of tegobuvir with a protease inhibitor, GS-9256, the majority of GT1a patients developed double-resistance mutations for these DAAs, with Y448H detected in seven out of eight GT1a patients, while RAVs C316Y and C445F were also detected in two GT1b patients [ 104 ]. The clinical development of tegobuvir was recently halted; however, an in vitro study recently demonstrated the potential of tegobuvir as a DAA due to its additive effect when examined with PIs or NNIs in inhibiting replicon models and significantly hindering the development of resistance mutations [ 105 ].…”
Section: Hcv Rdrp As a Target For Daasmentioning
confidence: 99%
“…Using mathematical models, we showed that superinfection and cure of infected cells are likely to be crucial mechanisms driving the extremely rapid expansion and turnover of resistant variants observed in the clinical data. Although superinfection and cure of infected cells have been demonstrated in vitro ( 33 37 , 41 ), our work suggests that these processes occur and play important roles in driving viral adaptation and persistence in vivo.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, we hypothesize that the continuous turnover of dominant mutants in the absence of treatment is mostly driven by intracellular competition among viral strains, as a result of superinfection (rather than competition for newly generated target cells). Previously, cure of infected cells has been demonstrated in in vitro studies ( 33 37 ). In vivo, the rapid second-phase viral declines under treatment were suggested to be attributable to cure of infected cells ( 32 , 38 ).…”
Section: Resultsmentioning
confidence: 99%